Large‐Scale Diffusion Barriers from CVD Grown Graphene. Issue 14 (4th August 2015) - Wirtz, Christian; Berner, Nina C.; Duesberg, Georg S.
<x xml:space="preserve">Abstract</x> Graphene has been long thought of as a perfect barrier material due to its impermeability to all gases as well as mechanical and chemical durability. Moreover, graphene layers are transparent and conductive, significantly widening the field of potential applications beyond simple barrier coatings. However, it is very challenging to realize such barriers on a macroscopic scale as immaculate large area films are not available. In this work, a highly effective oxygen gas barrier made from multiple layers of chemical vapor deposited graphene is presented. The individual graphene layers are stacked using a modified polymer‐assisted transfer method, avoiding polymer residue yielding an oxygen‐tight arrangement. A stack of three layers of graphene transmitted 6.9 cm3 m−2 d−1 of O2 which corresponds to 1.10 × 10−17 cm3 cm/cm2 s (cm Hg) when normalized to thickness and pressure. This is several orders of magnitude better than any macroscale graphene coating reported to date and performs on a level that can compete with most modern coatings while being much thinner and conductive.